Working with paper. (New York, F. Watts, 1971)
Illustrated instructions for making decorative paper items such as mobiles, animals, and jewelry, are color-coded to indicate degree of difficulty.
Keywords: Paper work -- Juvenile literature; Paper work; Handicraft